2015
DOI: 10.1089/ees.2014.0269
|View full text |Cite
|
Sign up to set email alerts
|

Number-Average Molecular Weights of Natural Organic Matter, Hydrophobic Acids, and Transphilic Acids from the Suwannee River, Georgia, as Determined Using Vapor Pressure Osmometry

Abstract: Vapor pressure osmometry (VPO) was used to measure the number-average molecular weights (M n ) of natural organic matter (NOM) that was isolated using reverse osmosis, hydrophobic acids (HPOA) that were isolated by adsorption on XAD-8 resin, and transphilic acids (TPIA) that were isolated by adsorption on XAD-4 resin. All samples were isolated from the headwaters of the Suwannee River in southeastern Georgia, USA, in May 2012. NOM, HPOA, and TPIA samples had M n of 634 -11, 583 -8, and 498 -7 g/mol, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
2
10
1
Order By: Relevance
“…Still, the detailed organization of HS remains a matter of debate: molecular weight measurements performed at different stages of extensive fractionation schemes suggest that HS can be regarded as macromolecules or slightly branched polymers that can coil or adopt an extended conformation according to solution properties [1] [22] [23] [24], whereas some Size Exclusion Chromatography experiments and NMR results suggest that HS correspond to supramolecular associations of small heterogeneous molecules that can be disrupted in the presence of organic acids [6] [10] [25] [71] [72] [73]. To account for the surface-active properties of HS and the enhanced solubility of hydrophobic organic compounds in their presence [26], such molecular aggregates have also been described as micelles with a hydrophilic exterior and a hydrophobic core [9].…”
Section: Introductionmentioning
confidence: 99%
“…Still, the detailed organization of HS remains a matter of debate: molecular weight measurements performed at different stages of extensive fractionation schemes suggest that HS can be regarded as macromolecules or slightly branched polymers that can coil or adopt an extended conformation according to solution properties [1] [22] [23] [24], whereas some Size Exclusion Chromatography experiments and NMR results suggest that HS correspond to supramolecular associations of small heterogeneous molecules that can be disrupted in the presence of organic acids [6] [10] [25] [71] [72] [73]. To account for the surface-active properties of HS and the enhanced solubility of hydrophobic organic compounds in their presence [26], such molecular aggregates have also been described as micelles with a hydrophilic exterior and a hydrophobic core [9].…”
Section: Introductionmentioning
confidence: 99%
“…Raeke et al (2016) recently found poor recovery of higher molecular weight organic matter by Oasis HLB, which was attributed to stronger sorption to the sorbent and consequently incomplete elution. Therefore, the poor recovery of HA compared to NOM may be due to differences in molecular weight, with HA typically having a larger molecular weight than NOM (Pavlik and Perdue, 2015).…”
Section: Doc Can Activate the Nf-κb Responsementioning
confidence: 99%
“…M n values determined by asymmetrical flow field-flow fractionation (AsFlFFF) using absorbance detection at 254 nm were 1,461 -7 Da for RFSW, 1,517 -8 Da for NOM, 1,471 -7 Da for HPOAs, and 1,095 -5 Da for TPIAs (Kuhn et al, 2014). AsFlFFF values tend to be much higher for DOM than are values determined by VPO (Pavlik and Perdue, 2014). The AsFlFFF values may be useful for comparison between samples but should not be thought of as true MWs.…”
mentioning
confidence: 96%
“…The ''molar absorptivity'' (e 280 ), which has been shown to correlate with HS aromaticity, was calculated from absorbance at k at 280 nm and DOC concentrations to be in L/ (mol C$cm): 486 for NOM, 461 for HPOAs, and 262 for TPIA. The number average MW (M n ) values determined by vapor pressure osmometry (VPO) (Pavlik and Perdue, 2014) were 634 g/mol for NOM, 583 g/mol for HPOAs, and 498 g/mol for TPIA. M n values determined by asymmetrical flow field-flow fractionation (AsFlFFF) using absorbance detection at 254 nm were 1,461 -7 Da for RFSW, 1,517 -8 Da for NOM, 1,471 -7 Da for HPOAs, and 1,095 -5 Da for TPIAs (Kuhn et al, 2014).…”
mentioning
confidence: 99%